(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The article deals with the issues of the procurement activities of the enterprise. It is shown that at the current level of economic development, the reliability of procurement management at manufacturing enterprises is the most important condition for ensuring the stability of development, as well as the timely and rhythmic implementation of production plans and product sales. It is noted that in order to improve the efficiency of procurement activities at the enterprise, it is achieved by using a set of measures based on a systematic and integrated approach. In the management of the procurement activities of enterprises, the use of such tools as regulated tools, as well as tools and methods that take into account the peculiarities of the functioning of the enterprise, create opportunities for optimizing the material flow at the initial stage of procurement and can significantly reduce this procedure.